Hellenistic and Roman bronze statuettes in the Ashmolean Museum - West, N (2016)
This thesis is an aetiological investigation of the Hellenistic and Roman figural bronze statuettes in the round that form part of the Ashmolean Museum’s antiquities collection. The collection serves as a lens through which to study aspects of ancient and modern receptions of Classical sculptural forms. This approach is based on the premise that the collection’s composition has been historically determined not only by how the modern parties responsible for its creation and growth responded to the sculptural forms and images recovered from antiquity, but also by how sculptural forms developed in Greece during the Classical and early Hellenistic periods were received by makers and users of bronze statuettes in antiquity. The thesis has three primary objectives: firstly, to produce a useful and informative catalogue of the Ashmolean Museum’s collection of Hellenistic and Roman figural anthropomorphic bronze statuettes in the round; secondly, to determine not only how that collection came to have the characteristics that it does, but also how the reception of ancient sculpture has historically affected the formation of collections of bronze statuettes and their compositions; thirdly, to use archaeological evidence of bronze statuettes to reconstruct possible contexts and to determine in greater detail the reception of canonical sculptural figure types in the form of small bronzes during the Hellenistic and Roman periods. Part I of the thesis deals with the modern contexts for the statuettes, investigating the collection history, pulling out its salient characteristics and then comparing these to other major collections to make informed observations about how and why specific types of statuettes have survived from antiquity and the roles that modern reception of antiquity has played in shaping collections. This leads to Part II, which attempts to reconstruct possible ancient contexts for the Ashmolean bronzes by looking at the archaeological evidence for their production, movement use and display. Part III uses some of the figures of dwarfs, Herakles and Hermes in the collection to develop case studies that examine aspects of the visual relationships that existed between small bronzes and classical sculpture from the Classical and early Hellenistic periods.